Utilizing smartphones for geospatial data collection and construction set out surveying - Lee, A.; Majhi, S.; Mukherjee, Abhijit (2017)
© 2017 Taylor & Francis Group, London. Smartphones on account of their accessibility and presence of sensors like GPS, magnetometer and accelerometer can be a useful for carrying surveying operations. In the present work, the precision of Smartphones for real time geospatial data collection in surveying environment for maintenance of local government asset and construction set out surveying is investigated. Improvement in the accuracy of geo-spatial location data by pairing smartphones with RTK (Real Time Kinetics) Network and GNSS (Global Navigational Satellite System) Receiver connectivity is observed. Besides, accuracy and reliability in measurement of horizontal distance, bearing angle and areas of closed traverse survey using smartphones has been investigated by comparison with a conventional surveying instrument. Overall, it can be concluded that a smartphone can be used for low precision surveying applications within civil engineering surveying where a quick survey is required for locating infrastructure assets, conducting maintenance inspections and providing a preliminary clearing area set out.